EFFECT OF CORN GLUTEN SUPPLEMENT TO LOW QUALITY ROUGHAGES TREATED WITH UREA ON CHEMICAL COMPOSITION AND IV VITRO DIGESTIBILITY - & Mohammed, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to determine the effect of corn gluten (0 and 9%) supplementation to low quality roughages (date palm frond, reeds, corn cobs and barley straw) treated with 5% urea on chemical composition and in vitro digestibility,The treatments were incubated for 0,20 and 30 days at ambient temperature (30-37 C°).The results showed that nitrogen content, cellulose, metabolizable energy(ME) dry matter InVitro digestibility (IDMD) and Organic matter InVitro digestibility (IOMD)were increased significantly (P<0.01).The dry matter (DM),organic matter(OM) ,neutral detergent fiber (NDF),hemicelluloses, Lignin and pH were significant decrease (P<0.01) in date palm frond by treated with urea and corn gluten.Nitrogen content, total digestible nutrients (TDN), ME, IDMD and IOMD had more(P<0.05) for corn cops treated with urea and corn gluten than un treated. The DM, OM,NDF, acid detergent fiber (ADF), cellulose and pH in corn cobs by treated with urea and corn gluten were Significant decreased (P<0.01). On the other hand, treated reeds resulted in increasing (P<0.01) in nitrogen content, hemecellulose, IDMD, IOMD, TDN and ME, and decreasing (P<0.01) in NDF, cellulose and ADF content. The result indicated that total nitrogen, IDMD, IOMD, ME and TDN improved significantly(P<0.01) by treated barley straw while OM content was decreased(P<0.01(.Furthermore the best incubation time which gave better improve nutrient value was associated with 20 and 30 days incubation time. We conclude from this study that it is possible to improve the nutritive value of low quality roughages by treated with urea and supplemented with corn gluten.